Functional (conversion) neurological symptoms: research since the millennium. Issue 8 (3rd June 2012) - Carson, Alan J; Brown, Richard; David, Anthony S; Duncan, Roderick; Edwards, Mark J; Goldstein, Laura H; Grunewald, Richard; Howlett, Stephaine; Kanaan, Richard; Mellers, John; Nicholson, Timothy R; Reuber, M; et al.
Abstract : Functional neurological symptoms (FNS) are commonly encountered but have engendered remarkably little academic interest. 'UK-Functional Neurological Symptoms (UK-FNS)' was an informal inaugural meeting of UK based clinicians in March 2011 with a variety of research and clinical interests in the field. This narrative review reflects the content of the meeting, and our opinion of key findings in the field since the turn of the millennium.